On the front line: Community nutrition programming - Gillespie, Stuart; Hodge, Judith (International Food Policy Research Institute, 2016)
Whatever advances have been made in terms of technologies, interventions, and their delivery platforms in recent decades, it is households and communities that remain on the front lines in combating malnutrition. During the past half century, several significant attempts have been made to initiate and implement community-based nutrition programs. This chapter assesses the evolution and performance of